Determinants of Total Factor Productivity: The cases of the main Latin American and emerging economies of Asia (1960 - 2015) (2018)
The objective of this paper was to explain the greater or lesser growth rate of total factor productivity, TFP, in the main East Asian and Latin American economies between 1960 and 2015. We found econometric evidence favorable to this hypothesis: the increase in public consumption expenditures, given the evolution of other factors, reduces the TFP. Other results of the econometric exercise, those that are related to hypothetical positive effects of public investment and imports on TFP were not as robust or as reliable as we would have expected.